PERANAN PEMIMPIN INFORMAL DALAM PEMBANGUNAN DESA (STUDI DI DESA PULAU TERAP KECAMATAN KUOK KABUPATEN KAMPAR TAHUN 2014) - Fajri, Algi; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Terap Village one of the villages located in the district of Kuok is a village that is still strong customs, religious and agrarian. The role of the informal leaders seemed so real in building public awareness in development, this is because the villagers Pulau Terap comes from the same tribe or homogeneous so that the role of informal leaders are needed to strengthen unity in the community. The formulation of the problem in this study how informal leadership roles in the development in the Pulau Terap village of Kuok District of Kampar Regency. This study aims to identify and explain the role of the Informal Leaders in Development in Pulau Terap Village istrict of Kuok. This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories.Based on this research, seen the role of informal leaders in rural development is very important amongst the people but not very effective in terms of informing and inviting the public to participate in development activities. In addition informal leaders often become donors in every building in the village. To increase the participation of community development need their leaders sinerginitas between formal and informal leaders,Keywords: Informal Leader, Development, Village